Rappresentazioni di realtà ai margini di Oslo in Alle utlendinger har lukka gardiner di Maria Navarro Skaranger e Tante Ulrikkes vei di Zeshan Shakar: kebabnorsk, glocalità e gangster ‘wannabe’ (Altre Modernità, 2022)
The article focuses on two contemporary Norwegian novels, Alle utlendinger har lukka gardiner by Maria Navarro Skaranger (2015) and Tante Ulrikkes vei by Zeshan Shakar (2017), and explores the concept of glocality, understood here as the coexistence between a strong attachment to the neighborhood of residence and the identification in the global youth subculture of rap and hip hop. The figure of the “wannabe” gangster, namely a person who acts or dresses like a gangster but who is not involved in crime, is subsequently taken into consideration. Both are behaviors that sociolinguistic studies have associated with Kebabnorsk speakers.
Keywords: Postmigration Literature; Satellite Town; Kebabnorsk; Glocality; Rap/Hip Hop; ‘Wannabe’ Gangster